Networks of support: factors contributing to successful inter-agency work with young people - Roaf, C (1999)
This study examines how agencies might work together more effectively to improve the life chances of young people who fall `through the net' of agency provision. Whatever the situation, the failure to co-operate challenges a democratic society and basic human rights. The problem occurs when individual primary care agencies either: • try to do on their own what can only be achieved by co-operation, or • fail to do anything because, in their view, the client's needs should be met by some other agency, or • only do what they can do on their own. The purpose of this study is to establish: • to what extent improvements in inter-agency co-operation would help agencies work more effectively with young people variously described as falling through the net, or on the margins of an agency's responsibility • what factors contribute to these improvements • what characterises effective models of inter-agency practice. The study finds that over the last thirty years, the legislative framework surrounding inter-agency co-operation for young people provides few examples of structures or procedures requiring agencies to co-operate. Where these exist, they have been set up in response to needs or crises of pressing concern at the time. Research into the practice of inter-agency work shows that successful inter-agency projects set up to meet the needs of those at risk of falling through the net follow a characteristic pattern. This led to the construction of a model based on the idea that successful inter-agency practice depends on the existence of collaborative activity at three interconnected levels: policy and planning; implementation, case work, research and training; networking/liaison. Projects supported at all three levels are more likely to be successful and survive than those which are not. This pattern can be replicated in different contexts and with different client groups to ensure effective co-ordination and redistribution of resources, and that a balance is held between preventative and proactive work. The model's key elements enable it to structure communication pathways within and between agencies, to co-ordinate activity in relation to a particular issue, to develop the interpersonal skills of participants and to provide feedback to policy makers. The research concludes that: • formal structures promoting inter-agency collaboration encourage agencies to innovate and to provide co-ordinated services for young people needing more support than can be provided by any one of them • inter-agency work has become a new area of professional and para professional expertise • models designed to help agencies meet the needs of people at risk can be applied to other projects set up to solve complex problems involving more than one department